Physical health of food consumers during the COVID-19 Pandemic - Oliveira, José (2021)
The present research aims to analyze the habits observed in the perception of the general physical health condition of Portuguese food consumers in the COVID-19 pandemic. The investiga- tion is focused on indicators such as weight, physical activity, and consumption habits through the adoption of healthy and not healthy food. Centered on a quantitative approach, the research is based on the application of a questionnaire to a sample of 741 Portuguese consumers, between November 2020 and February 2021, a period during which the most severe measures of social isolation were imposed by the Portuguese government, since the beginning of the pandemic. Moreover, the ques- tionnaire was applied to consumers over 18 years old. According to this population, and considering a 95% confidence level and a margin of error of 4%, the sample has a minimum of 601 responses. Being so, the results of this research are representative for the Portuguese food consumers. The theoretical model was estimated using Partial Least Squares (PLS) in the Smart PLS 3.0 software. The obtained results allowed us to conclude that the Portuguese perception of their weight did not change in the pandemic, despite showing that in general, the pandemic had a negative impact on their physical condition. On the other hand, the results show that the Portuguese associate the practice of physical exercise with physical well-being. Respondents also confirm a positive relationship between “positive eating behaviors (such as consumption of fruits and vegetables, low saturated foods and rich in monounsaturated and polyunsaturated fats” and water consumption) and “the perception of physical health in general”. On the contrary, respondents’ perception of the choice of negative eating behaviors (measured by the consumption of products with a high content of salt and sugar, snacks, and processed frozen and pre-cooked foods) have a negative impact on the “assessment of physical health, in the COVID-19 pandemic”. Hence, it was concluded that the Portuguese consider that an eventual increase in weight does not necessarily correspond to a perception of worse physical health; the practice of physical exercise and good eating habits corresponds to a perception of better physical health; the adoption of bad eating habits corresponds to the perception of bad physical health.